Strain‐Induced Reduction of Centrosymmetry in Rare‐Earth Iron Garnet Thin Films - EMK Ikball Ahamed; Hiroyasu Yamahara; Md Shamim Sarker; Haining Li; Kazuo Morikawa; Kohei Yamagami; Masaki Kobayashi; Munetoshi Seki; Hitoshi Tabata (Advanced Electronic Materials)
Abstract Rare‐earth iron garnets (RIG, R3Fe5O12) are insulating ferrimagnets with high inversion symmetry because of their centrosymmetric cubic crystal structure. However, this high centrosymmetry can be reduced by introducing a non‐uniform strain, leading to a tetragonally distorted lattice structure. In this study, the strain‐induced lattice distortions and symmetry‐breaking features are investigated in compressively strained Sm3Fe5O12 and tensile‐strained Lu3Fe5O12 thin films around critical thicknesses. Experiments indicate that tensile strain prevents the in‐plane epitaxy from relaxing, whereas compressive strain leads to easy relaxation after reaching a critical threshold triggered by misfit dislocations. A non‐zero orbital moment, a more than tenfold increase in coercivity, and an increase in Gilbert damping near the critical thickness indicate a reduction of spatial inversion symmetry without forming any misfit dislocations. It is speculated that strain energy in uniformly strained epitaxial thin films has been partially released when the thickness reached about the critical thickness. The proposed strain‐mediated reduction of centrosymmetry may pave the way to achieve controllable magneto‐dynamics in dislocation‐free tensile strained RIG thin films.